2019
DOI: 10.1039/c9sc01590f
|View full text |Cite
|
Sign up to set email alerts
|

Measuring proteins in H2O with 2D-IR spectroscopy

Abstract: 2D-IR spectroscopy is used to measure protein amide I bands in water, avoiding the need for deuteration. We show that H/D exchange affects protein vibrational relaxation dynamics and that the ability to perform 2D-IR in water enables blood serum protein analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
111
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(115 citation statements)
references
References 30 publications
3
111
0
Order By: Relevance
“…1c, 1d), where many absorption bands are observed which could be attributed to the proteins, such as: 2500-3500cm -1 from -OH, 2400-3200cm -1 from NH2, 1650cm -1 from the peptide bonds, and 800-1000 cm -1 from C-H [6] . However, due to the low concentration, they are mostly overlapped by the FTIR of the buffer solution PBS, which is dominated by water (0.1wt%NaCl +0.002wt%KCl +0.01wt%Na2HPO4 +0.002%wtKH2PO4 +99 + wt%H2O), such as: 2500-3500cm -1 from -OH stretching, 2250-2500cm -1 from H-O-H bending, 1650 cm -1 from -OH scissoring, and 800-1000 cm -1 from H2O liberation, which could neither be easily resolved by D2O replacement, [28,29] although absorption band at around 1630cm -1 does show some protein variation [6] . Fortunately, there exists a FTIR absorption band exclusively associated with the proteins, but not overshadowed by the solvent at 1550 cm -1 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1c, 1d), where many absorption bands are observed which could be attributed to the proteins, such as: 2500-3500cm -1 from -OH, 2400-3200cm -1 from NH2, 1650cm -1 from the peptide bonds, and 800-1000 cm -1 from C-H [6] . However, due to the low concentration, they are mostly overlapped by the FTIR of the buffer solution PBS, which is dominated by water (0.1wt%NaCl +0.002wt%KCl +0.01wt%Na2HPO4 +0.002%wtKH2PO4 +99 + wt%H2O), such as: 2500-3500cm -1 from -OH stretching, 2250-2500cm -1 from H-O-H bending, 1650 cm -1 from -OH scissoring, and 800-1000 cm -1 from H2O liberation, which could neither be easily resolved by D2O replacement, [28,29] although absorption band at around 1630cm -1 does show some protein variation [6] . Fortunately, there exists a FTIR absorption band exclusively associated with the proteins, but not overshadowed by the solvent at 1550 cm -1 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although studies of cataract samples were carried out post-mortem, a recent study has shown that 2D-IR spectroscopy could be applied to the molecular analysis of proteins in blood serum taken as part of a routine medical procedure. 42 Spectroscopic interrogation of biofluids is attractive as a label-free, minimally-invasive screening technology. 43 Biofluids, such as blood serum are generally easily obtained, with minimal patient discomfort, and they provide access to a large amount of potentially diagnostic chemical information, reporting as they do on metabolism.…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…It was demonstrated that 2D-IR spectroscopy can avoid this problem because, in contrast to IR absorption experiments, the 2D-IR amide I signature of proteins dominates that of water even at sub-millimolar protein concentrations. 42 This important result means that 2D-IR can be used to study the amide I band of protein containing samples without the need for expensive, time consuming deuteration of solvents. Equine blood serum was employed as a test system and the unique link between protein secondary structure and the 2D-IR amide I lineshape enabled differentiation of signals due to albumin and globulin protein fractions in serum and quantitative measurements of the biomedically-important albumin to globulin ratio (AGR) with an accuracy of ±4% across a clinically-relevant range.…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…2D-IR spectra of the isotope labelled amide I band have been shown to contain sufficient constraints to solve the structure of a large peptide 7 and although such comprehensive global structural determinations are best achieved by X-ray or NMR techniques, isotope labelled amide I 2D-IR is a unique site-specic probe of equilibrium protein structure and dynamics, 8 with applications demonstrated testing ion channel lter mechanisms 9 and amyloid aggregation. 10 For 2D-IR analysis of the amide I band of unlabelled proteins, 11,12 secondary structure determination ability is comparable to ultraviolet circular dichroism 13 and there is recent evidence of utility to this end in the analysis of blood serum samples 14 and eye cataracts. 15 In this paper, 2D spectra of the amide I band of proteins are measured using alternative laser pulse sequences involving IR and Raman processes.…”
Section: Introductionmentioning
confidence: 99%